GEOMORPHIC INDICES AND FAULT SEGMENTATION INDICATION OF MENANGA FAULT AT PESAWARAN, LAMPUNG - Hendrawan, Rezki Naufan; Draniswari, Windi Anarta; Bakhtiar, Agim Yustian; Widiatama, Angga Jati (Engineering Faculty Universitas Lampung, 2023)
Remote sensing and GIS are playing important roles in geomorphology and hazard risks analysis. Pesawaran area located near the Menanga Fault and recently on the risk of earthquake that happened along this fault.Â Thus, it is essential to investigate the area actively affected by Menanga Fault as preliminary research about hazard risk related to Menanga Fault. The morphometry method based on DEMNAS and Landsat 8 was applied to evaluate the zone affected by Menanga Fault, and fracture data analysis was conducted to consider the possibility of fault segmentation resulting from its mechanism. The study area can be divided into 3 zones; zone A is greatly affected by Menanga Fault activity, zone B is affected by Menanga Fault and Mt. Pesawaran development, and zone C is tectonically less affected. Zone A landforms were not only formed as a result of Menanga Thrust fault but also the strike-slip fault segment.Â Fault segmentation exists in this zone with different mechanisms (strike-slip and dip-slip), producing lineaments with different trends, and differentiation of river patterns.